(untitled) (Simbiótica. Revista Eletrônica, 2016)
This article’s purpose is to study the discussion of institutionalized situation of children and adolescents and the general objective is the discussion about the situation of children and adolescents in Brazil who are in shelters and have their right to family and community denied. The article’s methodology was literature review from books and scientific articles, as well as the National Plan for the Promotion, Protection and Defense of the Children’s Right to Family Living and Community and the Statute of Children and Adolescents. The discussion promoted in this article brought the child story elements in Brazil encompassing the issue of institutionalization. Was also part listed an overview of shelters in Brazil with an emphasis on southern Brazil, reaching the scene of the city of Ponta Grossa - PR. As a result we can list that the number of institutionalized children is still high even with the numerous laws that form the rights guarantee system. There was a need in changing the thinking of society with regard to institutionalized children and adolescents, as they are still targets of stigma. Keywords: shelter; child; adolescents; rights.